Progression of SEI & SEM Final Year Projects. - Khairul Hamimah Abas, editor 399952; Anita Ahmad, editor 486221; Shahdan Sudin, editor 273990; Khairul Hamimah Abas, contributor 399952; Ahmad Ridhwan Wahap, contributor 201780; Alaa A. Abu Zaiter, contributor 541738; Cheng, Siong Lim, contributor 647610; Fu, Seong Woon, contributor 647959; Chong, Jason Kin Chin, contributor 647960; Jong, Yung Sheng, contributor 647961; Mohamed Sultan Mohamed Ali, contributor 491888; Mohd. Ridzuan Ahmad, 1981-, contributor 643081; et al. (Johor Bahru, Johor : Pusat Pengurusan Penyelidikan (RMC) & PENERBIT UTM PRESS, 2014)
Includes bibliographical references and index.